Oral Manifestation Related to Drug Abuse : A Systematic Review: Manifetasi oral terkait penggunaan obat-obatan terlarang : Sebuah tinjauan sistematis - Djou, Rahmatia; Dewi, Tenny Setiani (TALENTA, 2019)
Drug abuse influences the pathological of oral diseases. There are scarce evidence-based data on the oral manifestations related to drug abuse. This systematic review aim to assess the oral manifestations related to drug abuse. Electronic databases were searched using keywords include oral manifestations and drug abuse. Observational studies published until September 2018 with the outcome of oral manifestations related to drug abuse were included. Data were extracted as percentage include drug type, route of administration, and oral manifestations. Study quality was assessed using the quartile score of Scopus index. The systematic review of 17 studies revealed that methamphetamine (53%), heroin (41%), cannabis (35%), and cocaine (35%) were the most frequent abused drugs from 10139 samples. The routes of administration include smoking (58%),inhalation (35%), injection (35%), and oral route (17%), with duration of use ranged from one year to forty years. The most significant of oral manifestations reported were periodontal diseases (76%), dental caries (76%), and xerostomia (41%). Adverse drug reaction in oral cavity may cause, directly or indirectly, immunosuppression, susceptibility to infections, and oral pathologies due to chemical composition and mechanism of action specifically to drug type related with duration of use and route of administration.